2012
DOI: 10.3748/wjg.v18.i38.5404
|View full text |Cite
|
Sign up to set email alerts
|

Different risk factors influence peptic ulcer disease development in a Brazilian population

Abstract: In our population, male gender was a risk factor for PU; ageing for GU, atrophy and metaplasia; and H. pylori of vacA m1 genotype for DU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
2
8
0
1
Order By: Relevance
“…Corroborating the results of the cited study, 28 no progressive neoplasia was found on the present UDE analysis.…”
Section: ■ Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Corroborating the results of the cited study, 28 no progressive neoplasia was found on the present UDE analysis.…”
Section: ■ Discussionsupporting
confidence: 90%
“…Although the study was conducted at a reference center, Suzuki et al 28 found a 6% prevalence of duodenal ulcer in patients with dyspeptic symptoms. This result may suggest an increased prevalence of duodenal ulcer in our patients, since the present study only included asymptomatic dyspeptic cases.…”
Section: ■ Discussionmentioning
confidence: 98%
“…Out of 146 males in the study, 4 were diagnosed with a malignant ulcer, whereas out of 51 female patients, malignancy was detected in 2 of them, male-to-female ratio in the studied patients was 2.86:1, which complies with the fact that peptic ulcer disease is more common in male sex compared to females also described by Rodrigo et al 7 The incidence of malignant ulcer in alcoholics was 3.37% compared to 0.92% in nonalcoholics.…”
Section: Discussionsupporting
confidence: 85%
“…H. pylori infection was demonstrated as an independent risk factor for histological gastritis,6 inflammation, and peptic ulcer 5,34,35…”
Section: Discussionmentioning
confidence: 99%